Treatment of Esophageal Hematoma After Left Atrial Appendage Occlusion: A Case Report - Cheng, Chaodi; Zhou, Yang; Wang, Yanjiang; Shi, Liang; Tian, Ying; Liu, Xingpeng (Frontiers in Cardiovascular Medicine, 2022)
Left atrial appendage occlusion (LAAO) is an alternative to oral anticoagulation therapy in patients with atrial fibrillation who are at high risk for bleeding and thromboembolic events. Transesophageal echocardiography (TEE) is the standard modality for intraprocedural imaging during LAAO. We report a rare case of extensive submucosal esophageal hematoma that developed after a TEE-guided LAAO procedure. The cause, management, and prevention of this complication are explored in depth in this report.